Using steps at the Si-SiO2 interface to test simple bond models of the optical second-harmonic response - MCGILP, JOHN (My University, 2007)
A simple bond model of the optical second-harmonic (SH) response from interfaces, which assumes a single axial component for each bond, is tested by comparing the response from different step structures at the Si?SiO2 interface. The response of native-oxide-covered vicinal Si(111), offcut by 3? towards , is compared with previous work on similar samples, but offcut by 5? in the opposite, , direction. The two offcuts have different step geometries, but the same terrace structure at the Si?SiO2 interface, while the bulk quadrupolar contributions from the two offcuts are related by simple geometric factors, thus significantly constraining the number of adjustable parameters. The bond model is tested against experiment for the eight sample rotation plots obtained by permuting s- and p-polarization combinations. The constrained fit is found to be too poor to justify the extraction of quantitative information. Kleinman symmetry is shown to be a necessary, but not sufficient, condition for determining whether such a simple bond model can be applied, quantitatively, to the SH response from interfacial structures. It remains possible that quantitative information may be obtained from axial bond models by including local field effects in a simple way.
PUBLISHED
Keywords: Condensed matter physics; Optics